Peran mediasi kepercayaan konsumen dalam hubungan antara fitur COD-cek dulu, retur, dan keputusan pembelian di aplikasi Shopee - Verawita, Risma Hardena; Sedyati, Retna Ngesti; Ratna S, Prima (Nur Science Institute, 2026)
The rapid growth of e-commerce has transformed consumer shopping behavior; however, online transactions remain vulnerable to risks such as fraud and product mismatch, which may reduce trust and influence purchase decisions. Shopee provides COD–Check First and Return features to enhance transaction security and consumer trust. This study aims to examine the effect of these features on purchase decisions, with consumer trust as a mediating variable. This study adopts a quantitative approach using questionnaires and involves 190 respondents selected through purposive sampling. Data were analyzed using SmartPLS. The results show that COD–Check First and Return significantly influence consumer trust. Consumer trust, in turn, significantly affects purchase decisions and mediates the relationship between both features and purchase decisions. Privacy is identified as the most dominant factor in the COD–Check First feature. At the same time, exchange leniency (ease of return/exchange) is the most influential factor in the Return feature, enhancing consumers’ sense of security and confidence in transactions.